The naked truth: a comprehensive clarification and classification of current 'myths' in naked mole‐rat biology. (3rd September 2021) - Buffenstein, Rochelle; Amoroso, Vincent; Andziak, Blazej; Avdieiev, Stanislav; Azpurua, Jorge; Barker, Alison J.; Bennett, Nigel C.; Brieño‐Enríquez, Miguel A.; Bronner, Gary N.; Coen, Clive; Delaney, Martha A.; Dengler‐Crish, Christine M.; et al.
ABSTRACT: The naked mole‐rat ( Heterocephalus glaber ) has fascinated zoologists for at least half a century. It has also generated considerable biomedical interest not only because of its extraordinary longevity, but also because of unusual protective features (e.g. its tolerance of variable oxygen availability), which may be pertinent to several human disease states, including ischemia/reperfusion injury and neurodegeneration. A recent article entitled 'Surprisingly long survival of premature conclusions about naked mole‐rat biology' described 28 'myths' which, those authors claimed, are a 'perpetuation of beautiful, but falsified, hypotheses' and impede our understanding of this enigmatic mammal. Here, we re‐examine each of these 'myths' based on evidence published in the scientific literature. Following Braude et al ., we argue that these 'myths' fall into four main categories: ( i ) 'myths' that would be better described as oversimplifications, some of which persist solely in the popular press; ( ii ) 'myths' that are based on incomplete understanding, where more evidence is clearly needed; ( iii ) 'myths' where the accumulation of evidence over the years has led to a revision in interpretation, but where there is no significant disagreement among scientists currently working in the field; ( iv ) 'myths' where there is a genuine difference in opinion among active researchers, based on alternative interpretations of the available evidence. The term 'myth' is particularly inappropriate when applied to competing, evidence‐based hypotheses, which form part of the normal evolution of scientific knowledge. Here, we provide a comprehensive critical review of naked mole‐rat biology and attempt to clarify some of these misconceptions.